A CRITICAL REVIEW ON GAJAPIPPALI WITH SPECIAL REFERENCE TO SAMHITA GRANTHAS - Nigamanand, *Bal; Suresh, Chaubey; Ramesh Chandra, Tiwari; Harsh Bardhan, Naithani (International Journal of Ayurveda and Pharma Research, 2016)
Herbal medicines is becoming popular worldwide, whereas Ayurveda is respected, but not accepted globally as a system of medicine to be prescribed in the treatment of ailments. Today In the developing countries many drugs are commonly used as herbal origin. The Vedic literatures indicate mainly about the utility of single herbs in management of common diseases. Samhita granth such as Brihatryee which includes Charak Samhita, Susrut Samhita, Vaghbhatta Samhita and Laghutrayee which includes Sarangdhar Samhita, Bhav prakash Samhita & Madhav Nidan, some other Samhitas such as Bhel Samhita, Harit Samhita, Kashyap samhita, which indicates the utility of single herbal drugs as well as the compound formulation in different diseases. Gajapippali is one of the most valuable drug which is frequently described in the different Samhitas as well as Nighantus, which shows its leading importance and wide utility in different therapeutics. Gajapippali belonging to family Araceae is a large epiphyte climbing shrub, rooting freely from the stem, marked with annular scars of fallen leaves. The fruits of Gajapippali shows Anthelmintic, Antibacterial, Anti-inflammatory, Analgesic, Anti-asthamatic, Antimicrobial, Cytostatic, Anti-oxidant activities. This herb has been given special appreciation in Ayurveda due to versatile therapeutic benefits. This paper provides detail description of Gajapippali in Brihatryee as well as Laghutrayee and the efficiency in various disorders.